Association between Household Food Consumption and Dietary Intake of Children (3-6 Years) In the Asesewa Sub-District - Tandoh, I. (University of Ghana, 2015)
Background: Household food consumption is a dynamic process that may influence the dietary intake and nutritional status of children living in the household. Children in their first five years are nutritionally vulnerable given their increased energy and nutrient needs. As these children are completely weaned and depend solely on household foods, less attention might be paid to the adequacy and quality of diet as compared to when they were receiving complementary foods. Objective: Determining the strength of association between household dietary diversity and child dietary diversity was thus the subject of investigation in this study. Methodology: A cross sectional survey was used to obtain data from 165 caregiver-child pairs from seven (7) randomly selected communities in the Asesewa sub-district. Structured questionnaires were used to solicit information on background characteristics and nutritional knowledge of caregivers; dietary data for the child was obtained using a single 24-hour recall method and a seven (7) day food frequency questionnaire. Household dietary data was also assessed with a seven (7) day food frequency questionnaire. Finally, height and weight measurements of both caregiver and child were taken (using standard procedures) and anthropometric indices (BMI-for-age and height-for-age) were computed. The relationships/associations between the independent variables (household dietary diversity, nutritional knowledge of caregivers) and dependent variables (child dietary diversity, height- for-age and BMI-for-age) were examined using Chi-square test and logistic regression employed to assess the strength of association after accounting for certain factors of interest. Results: Results indicated that, at least 90% of all households and children consumed more from starchy staples compared to other food groups. Diets were also low in dairy products and meat products having about 44.2% and 38.8% of participants respectively consuming them. Households had a mean household dietary diversity of 9.88 ± 1.7 out of 12 food groups and about 66% of the households had a high dietary diversity. The mean child dietary diversity was 6.75 ± 1.3 out of 9 food groups, and 58.2% of them were found to have a high dietary diversity. Meals provided by the household contributed to a majority of the children meeting or exceeding the EAR for protein, energy and carbohydrate but few meeting their requirement for vitamin C (27.3%) and calcium (3.6%). The prevalence of stunting (23.6%), underweight (4.2%) and overweight (3%) reported in the study were lower than estimates from national level and other studies. Studies provided evidence of a significant association (p<0.001) between household dietary diversity and child dietary diversity but no significant association with nutritional status of the children. Households with high dietary diversity had an almost six-fold likelihood of having children with high dietary diversity compared to households with low dietary diversity (OR: 5.7; CI: 2.78 - 11.84). The nutritional knowledge of the caregivers assessed had a marginal significant association with child dietary diversity (p=0.05). There was a tendency for caregivers with high nutritional knowledge to be more likely to have children with high dietary diversity (OR: 1.8; CI: 0.98, 3.44). Conclusion: The study showed a significant association between household dietary diversity and child’s dietary diversity.
Thesis (MPhil.) - University of Ghana, 2015